2004
DOI: 10.1089/105072504323150723
|View full text |Cite
|
Sign up to set email alerts
|

Increased Intensities of Fas Expression on Peripheral T-Cell Subsets in Severe Autoimmune Thyroid Disease

Abstract: Fas (CD95)-Fas ligand (FasL; CD178)-induced apoptosis is necessary for the maintenance of self-tolerance. To clarify whether or not any abnormalities in the Fas-FasL system exist in patients with autoimmune thyroid disease (AITD), we examined the expression of Fas and FasL on peripheral T lymphocytes by three-color flow cytometry in 113 patients with AITD and 49 healthy controls. The intensities of Fas expression in both CD4(+) and CD8(+) T cells decreased in thyrotoxic patients with Graves' disease (GD), but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…Such a trend was also found in the control group but the correlation was not statistically significant, probably due to the small number of subjects. Similar findings were reported by Maruoka et al in euthyroid patients with AITD and healthy subjects (32). It appears that more cells express Fas with age and this may become more prominent in HT, a condition associated with a higher degree of apoptosis in relation to GD.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Such a trend was also found in the control group but the correlation was not statistically significant, probably due to the small number of subjects. Similar findings were reported by Maruoka et al in euthyroid patients with AITD and healthy subjects (32). It appears that more cells express Fas with age and this may become more prominent in HT, a condition associated with a higher degree of apoptosis in relation to GD.…”
Section: Discussionsupporting
confidence: 88%
“…However, the lack of FasL expression by the same cells may prevent their elimination by apoptotic death. In this regard, a previous study also reported an increased proportion of Fas-expressing CD4 cells in untreated GD while expression of FasL was not detected (32).…”
Section: Discussionmentioning
confidence: 72%
“…Immune differences that underlie differences in the severity and intractability of these diseases remain unclear, and disease severity and intractability are difficult to predict. However, we have shown that particular lymphocyte subsets [4][5][6][7] and serum soluble CD8 [8] are related to the severity and intractability of these diseases. The levels of TSH receptor antibody (TRAb), IL-4, and IgE are also reported as the factors involved in the prediction of remission in GD [9,10].…”
mentioning
confidence: 98%
“…Two typical AITDs are Hashimoto's disease (HD) and Graves' disease (GD), and with either of these diseases the lymphocytes infiltrate the thyroid of patients [1][2][3][4]. We previously reported differences between the proportions of particular lymphocyte subsets in the thyroid and peripheral blood and suggested involvement of these subsets in the pathogenesis of AITD [5][6][7][8][9][10]. We have also reported the association between the polymorphism of interferon-γ gene and the severity of HD [11].…”
mentioning
confidence: 99%